A process of elimination? Reviewing the fragmented settlement record of eastern Pictland and its implications for future research - Reid, Vanessa (Medieval Settlement Research, 2021)
Across Scotland’s eastern mainland, evidence of early medieval settlement is varied and diffuse. Structural remains have proven particularly elusive, and our understanding of the relationship between sites, and the function of settlements in general, remains limited. Preservation has played a major role in the creation of this record and whilst contributing factors are routinely identified at the site-level, efforts to assess their prevalence have been virtually non-existent. Through a review of excavation literature, this paper collates evidence for the major factors impacting the survival of early medieval settlement remains and considers how such factors have influenced our interpretation of the archaeological record to date. The study then looks at the future of these sites in the wake of climate change and considers what techniques and strategies we may use to try and overcome the current theoretical and methodological hurdles.